Family Functioning, Peers Support, and Future Orientation in Marriage in Teenagers - Elinter Natalina Silalahi; Missiliana Riasnugrahani; Tery Setiawan (‎‎‎TAZKIYA Journal of Psychology, 2023)
Adolescents' future orientation toward marriage refers to the subjective ideas they form about the marriage they want in the future, including how they think, explore, and plan their lifetime development journey concerning marriage. Teenagers who lack future orientation in marriage frequently engage in promiscuity, unhealthy romantic relationships, and early marriages, which often result in divorce. For their future marriage to be successful, adolescents must develop a future-oriented marriage. This study examines how family function and peers support can predict the development of future orientation in marriage in class XII students of private schools in Tangerang City. This research explains the essential components needed in preparing for future orientation marriage, including romantic relationships. Through the convenience sampling technique, 212 students took part in the study. This study used three questionnaires with good validity and reliability: The McMaster Family Assessment Device (MMFAD), Peers Support, and The Prospective Life Course (PLC) Questionnaire – Future Marriage and Family. With hierarchical regression analysis techniques, this study shows that family functioning, peers support, and gender are correlated with future orientation-marriage. Students who believe that their families have healthy and effective structures, organizations, and patterns of interaction between family members are better able to develop a more focused and clearer subjective picture of the future in the field of marriage. This study also shows that students who receive high peers support are more successful in developing a clear and focused future orientation marriage. Based on this research, we suggest examining the future orientation-marriage to a wider target population using a random sampling technique so the result will have a broader generalization.